2006
DOI: 10.1038/sj.bdj.4814261
|View full text |Cite
|
Sign up to set email alerts
|

The impact of clinical audit on antibiotic prescribing in general dental practice

Abstract: • Describes an audit undertaken in the East of England on antibiotic prescribing in general dental practice.• The protocols of an original North West of England audit published in 2001 were deliberately replicated, in order to be able to pool the data and obtain a sample size of at least 1% of all UK dentists.• The combined Regional results confi rm that clinical audit reduces both the number of errors made by dental practitioners when writing out a prescription, as well as the number of those which are issued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
79
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 36 publications
(33 reference statements)
3
79
0
7
Order By: Relevance
“…These findings indicate a lack of knowledge and a misunderstanding of the involved pathologies, the impairment of the host defenses, the indication of prophylactic antibiotherapy, and the need to educate dentists on current prescription guidelines to favorably change their prescription behavior. 15 However, age is an important factor to consider because the complications associated with adverse effects resulting from the use of antibiotics can be more serious in very young and old patients. At least two previous studies reported that antibiotics were prescribed inappropriately to children most probably in a preventative proactive manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate a lack of knowledge and a misunderstanding of the involved pathologies, the impairment of the host defenses, the indication of prophylactic antibiotherapy, and the need to educate dentists on current prescription guidelines to favorably change their prescription behavior. 15 However, age is an important factor to consider because the complications associated with adverse effects resulting from the use of antibiotics can be more serious in very young and old patients. At least two previous studies reported that antibiotics were prescribed inappropriately to children most probably in a preventative proactive manner.…”
Section: Discussionmentioning
confidence: 99%
“…7 , 8 , 15 These results were not surprising because it was previously observed that dentists were reticent on prescribing antibiotics for the management of localized swellings: Despite a course given to dentists on the current prescribing guidelines, the level of unjustifi ed prescriptions after the course increased in the presence of a localized swelling. 15 In this study, a proper decision with regards to prescribing antibiotics or refraining from prescribing them was made for 19 and 22 patients respectively, corresponding to 48.3% of patients with an acute dentoalveolar abscess. Within this context, antibiotics were dispensed inappropriately to 16/42 patients (38.1%) with a chronic dentoalveolar abscess; antibiotics were not administered rightfully to the 26/42 remaining patients with a chronic abscess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite significant reductions in prescribing habits following education, it is still apparent that excessive prescriptions are being issued. 16,[18][19] Note has also been made of the vulnerability of general dental and medical practitioners in relation to such inappropriate prescribing in terms of potential litigation. 21 A study by Kuriyama et al 15 highlights the excellent success rates in achieving stabilisation and improvement in the clinical situation following surgical drainage of the dentoalveolar infection along with rational prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…7 A number of audits have been carried out looking into the prescribing habits of general dental and general medical practitioners. [15][16][17][18][19][20] Overwhelmingly these show that the antimicrobial prescribing habits are high when managing patients with acute dental pain, whether or not there is frank infection involved, and that there is wide variation in the type of antimicrobial prescribed, its dose and duration. They also highlight the lack of guidelines suggesting appropriateness in prescribing and illustrate how effective education is in reducing unnecessary prescriptions.…”
Section: Discussionmentioning
confidence: 99%